Phylogenetic systematics of dart-poison frogs and their relatives (Amphibia: Athesphatanura: Dendrobatidae) - Grant, Taran; Wheeler, Ward C.; Frost, Darrel R.; Caldwell, Janalee P.; Gagliardo, Ron; Haddad, Célio F.B. [UNESP]; Kok, Philippe J.R.; Means, D. Bruce; Noonan, Brice P.; Schargel, Walter E. (American Museum of Natural History (BioOne sponsored), 2006)
The known diversity of dart-poison frog species has grown from 70 in the 1960s to 247 at present, with no sign that the discovery of new species will wane in the foreseeable future. Although this growth in knowledge of the diversity of this group has been accompanied by detailed investigations of many aspects of the biology of dendrobatids, their phylogenetic relationships remain poorly understood. This study was designed to test hypotheses of dendrobatid diversification by combining new and prior genotypic and phenotypic evidence in a total evidence analysis. DNA sequences were sampled for five mitochondrial and six nuclear loci (approximately 6,100 base pairs [bp]; x=3,740 bp per terminal; total dataset composed of approximately 1.55 million bp), and 174 phenotypic characters were scored from adult and larval morphology, alkaloid profiles, and behavior. These data were combined with relevant published DNA sequences. Ingroup sampling targeted several previously unsampled species, including Aromobates nocturnus, which was hypothesized previously to be the sister of all other dendrobatids. Undescribed and problematic species were sampled from multiple localities when possible. The final dataset consisted of 414 terminals: 367 ingroup terminals of 156 species and 47 outgroup terminals of 46 species. Direct optimization parsimony analysis of the equally weighted evidence resulted in 25,872 optimal trees. Forty nodes collapse in the strict consensus, with all conflict restricted to conspecific terminals. Dendrobatids were recovered as monophyletic, and their sister group consisted of Crossodactylus, Hylodes, and Megaelosia, recognized herein as Hylodidae. Among outgroup taxa, Centrolenidae was found to be the sister group of all athesphatanurans except Hylidae, Leptodactyidae was polyphyletic, Thoropa was nested within Cycloramphidae, and Ceratophryinae was paraphyletic with respect to Telmatobiinae. Among dendrobatids, the monophyly and content of Mannophryne and Phyllobates were corroborated. Aromobates nocturnus and Colostethus saltuensis were found to be nested within Nephelobates, and Minyobates was paraphyletic and nested within Dendrobates. Colostethus was shown to be rampantly nonmonophyletic, with most species falling into two unrelated cis- and trans-Andean clades. A morphologically and behaviorally diverse clade of median lingual process-possessing species was discovered. In light of these findings and the growth in knowledge of the diversity of this large clade over the past 40 years, we propose a new, monophyletic taxonomy for dendrobatids, recognizing the inclusive clade as a superfamily (Dendrobatoidea) composed of two families (one of which is new), six subfamilies (three new), and 16 genera (four new). Although poisonous frogs did not form a monophyletic group, the three poisonous lineages are all confined to the revised family Dendrobatidae, in keeping with the traditional application of this name. We also propose changes to achieve a monophyletic higher-level taxonomy for the athesphatanuran outgroup taxa. Analysis of character evolution revealed multiple origins of phytotelm-breeding, parental provisioning of nutritive oocytes for larval consumption (larval oophagy), and endotrophy. Available evidence indicates that transport of tadpoles on the dorsum of parent nurse frogs-a dendrobatid synapomorphy-is carried out primitively by male nurse frogs, with three independent origins of female transport and five independent origins of biparental transport. Reproductive amplexus is optimally explained as having been lost in the most recent common ancestor of Dendrobatoidea, with cephalic amplexus arising independently three times. © American Museum of Natural History 2006.
Keywords: Alytes obstetricans; Amphibia; Anura; Centrolenidae; Ceratophryinae; Colostethus; Crossodactylus; Dendrobates; Dendrobates auratus; Dendrobatidae; Hylidae; Hylodes; Mannophryne; Megaelosia; Minyobates; Nephelobates; Phyllobates; Telmatobiinae; Thoropa